Late quaternary palaeoecology of the central and marginal uplands of the Karoo, South Africa - Sugden, Jean Mary (Department of Environmental and Geographical Science, 2016)
Pollen analysis of organic sediments from vleis in upland areas of the Central and marginal Karoo has provided a vegetation history spanning the late Quaternary in the Winterberg, Sneeuberg, Nuweveldberg and Cederberg Mountains. Fossil pollen studies indicate moist conditions at the beginning of the Holocene, followed by a drier period. The second half of the Holocene (4 600 BP) is characterised by moister conditions, becoming drier towards the present and resulting in a decline in grasslands and an increase in Karoo-bushes. In the western Cape, the late Pleistocene (15 000 to 10 000 BP) was characterised by conditions moister than the present. This was followed by a drier period which ameliorated in the late Holocene. Although climatic fluctuations occurred, fynbos has been maintained in situ throughout the sedimentation period (14 600 BP), highlighting the dominant role of the substrate and secondary importance of climate. Climatic changes caused a shuffling of plant communities within the Fynbos Biome - this long uninterrupted history may be one reason for the high species diversity of fynbos. San hunter-gatherers, who occupied southern Africa prior to 4 000 BP, had a negligible impact on the vegetation. Khoi herders, who were first documented in the fossil record about 1 800 BP, had a slight impact on the vegetation, particularly by altering the fire regime. However, the arrival of European Trekboers some four hundred years ago had a significant effect on the environment. Although the general climatic trend in the Karoo is one of a drier phase, the decline in grasses and eastward movement of xeric Karroid elements has been accelerated due to mismanagement and sedentary farming techniques. An extensive contemporary pollen rain study has been undertaken to examine the representivity of these fossil pollen data. The investigation shows that contemporary pollen rain is a good reflection of the vegetation communities in the Karoo and Cederberg. Multiple discriminant analysis compares fossil pollen assemblages with contemporary pollen spectra and proved useful for determining whether modern analogues exist for the fossil pollen assemblages. TWISA confirmed the zones derived from discriminant analysis. Environmental changes have occurred in the Karoo during the late Quaternary, resulting in fluctuations and changes in vegetation patterns which have been accelerated in the recent past by human activity. Bibliography: pages 293-318.